Improvement of native perennial forage plants for sustainability of Mediterraean farming systems. Lucerne (Medicago sativa) breeding work in south Tunisia - Loumerem M.; Tavares de Sousa M.M.; Annicchiarico P.; Pecetti L.; Hayek T.; Boubakri C. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Lucerne (Medicago sativa) is the most important fodder crop in the oases of Tunisia. A total of 20 accessions from representative 'Gabssia' landraces were collected during the growing season of 2004 and evaluated ex situ on IRA experimental fields in Médenine and Gabes. Considerable variation was observed for all the characters studied according to the descriptors published by CEC and IBPGR (1984). For most variables, in particular yield, a significant difference was obtained between accessions. A new breeding programme was initiated in IRA (Institut des Régions Arides) within the PERMED project - PL 509140, 2004. Ideotypes collected from different oasis environments were used for plant breeding and selection of new varieties. A selection method was developed to select alfalfa for drought resistance in IRA Gabes and for salt resistance in IRA Médenine.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)